Strategies for Improving the Performance of Civil Servants (ASN) Through the E-Performance Application at the Regional House of Representatives (DPRD) Secretariat of Sidoarjo Regency - Almira Dhevany; Trenda Aktiva Oktariyanda; Meirinawati M; Eva Hany Fanida (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The implementation of a digital-based performance management system through the E-Kinerja application is a government effort to improve the productivity and accountability of Civil Servants (ASN). This study aims to analyze the strategy for improving ASN performance through the E-Kinerja application using strategic management indicators proposed by Robbins and Coulter (2016), including mission, objectives, and strategy identification, internal and external environmental analysis, strategy formulation, implementation, and evaluation. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving structural officials, personnel staff, and ASN users of the E-Kinerja application. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the strategy for improving ASN performance through E-Kinerja has been implemented effectively. Leadership support, the facilitator system in each unit, intensive communication, and continuous monitoring and feedback are the main supporting factors. Internal strengths include human resources that are adaptive to technology, while differences in digital literacy remain a challenge. Externally, national regulations and regional digitalization policies serve as opportunities, whereas public pressure and technical system constraints pose potential threats. Continuous evaluation utilizing E-Kinerja data supports performance improvement and strategic decision-making.